2020
DOI: 10.1111/jmwh.13063
|View full text |Cite
|
Sign up to set email alerts
|

Refining Trauma‐Informed Perinatal Care for Urban Prenatal Care Patients with Multiple Lifetime Traumatic Exposures: A Qualitative Study

Abstract: Introduction Because lifetime trauma exposure has been linked to multiple adverse pregnancy outcomes, there is a need for all perinatal care providers to be versed in trauma‐informed care practices. However, there are few data to guide trauma‐informed practice during the perinatal period. The objective of this study was to refine ongoing development of a trauma‐informed care framework for perinatal care by conducting a qualitative study of all trauma experiences and preferred screening practices of pregnant pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Similar toWhite et al (2016) findings, women in our study indicated a desire that HCPs define ACEs, explain the purpose of the screening, and provide reassurance that screening is routine and confidential. They also preferredPre-F I G U R E 2 Recommended Strategies for Implementing ACEs Screening in Prenatal Care Settings screening occur after a trusting relationship is established with the HCP which is consistent with prior studies(Gokhale et al, 2020;Sobel et al, 2018). Yet, unlikeSobel et al's (2018) findings which indicated…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Similar toWhite et al (2016) findings, women in our study indicated a desire that HCPs define ACEs, explain the purpose of the screening, and provide reassurance that screening is routine and confidential. They also preferredPre-F I G U R E 2 Recommended Strategies for Implementing ACEs Screening in Prenatal Care Settings screening occur after a trusting relationship is established with the HCP which is consistent with prior studies(Gokhale et al, 2020;Sobel et al, 2018). Yet, unlikeSobel et al's (2018) findings which indicated…”
mentioning
confidence: 65%
“…Women disclosed if they had a trusting relationship with their provider and expected the information to be on their charts so other providers would be aware of their history. Some developed a birth plan to help with difficult aspects of the birth and expected the healthcare team to be aware of the plan Gokhale et al (2020). examined childhood adversities from a broader lens in their qualitative study of 30 women receiving care in one Chicago clinic.…”
mentioning
confidence: 99%
“…Implementing trauma-informed maternity practices and training can promote positive interactions based on respect, empowerment and collaboration [ 38 ]. A qualitative study from the USA on women who had experienced multiple lifetime traumatic exposures highlighted the importance of developing trusting relationships with empathetic HCP as an opportunity to disclose trauma and to have positive maternity experiences [ 60 ]. Midwifery models of continuity of care need to be expanded to include women with a previous caesarean and be made available to more women across Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of sexual dysfunction among women with a history of trauma and the high prevalence of sexual or physical trauma among women generally, when performing any genital examination, a trauma-informed approach is recommended. 43…”
Section: Laboratory Testing and Physical Examinationmentioning
confidence: 99%